Characterization and Agreement Between Application of Mobile Ecological Momentary Assessment (mEMA) and Accelerometry in the Identification of Prevalence of Sedentary Behavior (SB) in Young Adults - Romanzini, Catiana Leila Possamai; Romanzini, Marcelo; Barbosa, Cynthia Correa Lopes; Batista, Mariana Biagi; Shigaki, Gabriela Blasquez; Ronque, Enio Ricardo Vaz (Frontiers in Psychology, 2019)
New technologies able to identify the sedentary behavior (SB), such as the Mobile Ecological Momentary Assessment (mEMA) still need to be investigated. The aim of this study was to describe sedentary behavior (SB) in the physical, social and environmental contexts and verify the agreement between the mEMA and accelerometry in the identification of SB in young adults. During seven days, 123 young adults used concomitant mEMA and Actigraph wGT3xBT accelerometer. Data of 2262 mEMA prompts and respective count values in each minute (five minutes previous to prompt) were included in the analyses. Descriptive and comparative statistics were used in analyses using the SPSS 20.0 software. The physical context at home was the highest occurrence of SB (46.3%) and the main activity was “watching TV/movies” (29.7%). The main social context related to SB was “staying alone” (49.6%). The main assertions related to the participants' environmental context were: "I appreciate the comfort of electronic devices when I am at home" (86.2%). mEMA identified the presence of SB in 78.1% of prompts, while accelerometry identified 70.9% (PABAK=0.42). High values for the presence of SB were observed (sensitivity = 84%) and lower in the absence of SB (specificity = 38%). The study demonstrates the viability of mEMA use to obtain information about the occurrence of SB in contextual factors and good sensitivity to identify the presence of SB in young adults. The combined use of these methods is suggested in future studies about SB in young adults.